IMPLEMENTASI KEBIJAKAN KARTU IDENTITAS ANAK (KIA) DI KECAMATAN MIJEN KOTA SEMARANG - Ainun Nisa, Isnanda; Lituhayu, Dyah; Kismartini, Kismartini (Journal of Public Policy and Management Review, 2024)
Child Identity Card is a program issued by the government through Minister of Home Affairs Regulation Number 2 of 2016 concerning Child Identity Card. Mijen Subdistrict is one of the most outlying subdistricts in Semarang City, so KIA monitoring is not carried out optimally. The purpose of this research is to determine the implementation of KIA policy in Mijen Subdistrict, Semarang City and it's supporting and inhibiting factors. This research method is a qualitative method using research subjects as many as 5 informants consisting of Semarang City Population and Civil Registration Dispendukcapil staff, Mijen District TPDK staff, and the Mijen District residents. The accuracy of the policy has not been optimal because the public does not yet know the purpose of creating KIA. The implementation was correct because the Semarang City and Mijen District Population and Civil Registry Services as program managers had carried out their duties and roles well. The accuracy of the target can be seen from determining who should carry out KIA is child aged 0-17 years old. Environmental accuracy is considered to be appropriate even though it is not optimal because the dissemination of information is only about the requirements and flow of making KIA, but the more important about KIA program partnership is not disseminated. The accuracy of the process can be seen from indications of the readiness of the public and program implementers in understanding, accepting and being ready to be part of the program. In this case, the accuracy of the program implementation process was not optimal, the process was slow due to the public feeling less enthusiastic due to the lack of socialization and promotion, especially about the benefits of making KIA.